The Effectiveness of Caricature Image on Students Argumentative Writing in Higher Education - Darwin Effendi; Juaidah Agustina; Muhammad Ali (STAI Hubbulwathan Duri, 2023)
The aim of this study was to assess the efficacy of caricature image media in enhancing students' proficiency in argumentative writing. This study employed a quantitative experimental research methodology, specifically utilising a one-group pretest-posttest experimental design. The research was conducted in the Indonesian Language Education programme at a private university in Palembang during the academic year 2022/2023. The sample in this study was 29 semester 1 students (M = 2 and F = 27). The research data was taken through the process of observation, documents and tests. The data on the results of the written test were analyzed using the t-test for the treatment and experimental groups. This is a Paired Sample t-test. The results of the t-test obtained a t-count of 8.57 and the value of the t-table at dk (0.05)(29) was 2.048 with a significance level of 0.000. Because the calculated t value is greater than t table 8.57 2.048, it can be concluded that there is an influence of caricature image media on the learning outcomes of argumentative writing. While the average difference between the posttest and pretest is 4.75. From this average difference, it can be seen that the percentage increase was 47.11%. From the overall results of the presentation, it can be seen that the media of caricature images has a fairly good positive impact on the results of argumentation writing.